Social integration and mental health of Somali refugees in the Netherlands: the role of perceived discrimination - Emma Kuppens; Thijs van den Broek (BMC, 2022)
Abstract Background We assess whether social integration is associated with mental health among Somali refugees in the Netherlands, and how this association is shaped by perceived discrimination. Methods We performed linear regression and formal mediation analyses on Survey Integration Minorities data (n = 417) to assess whether the effects of two facets of social integration - Dutch language proficiency and informal contacts with natives - on mental health were mediated or suppressed by perceived discrimination. Results Dutch language proficiency was positively associated with mental health, but also with perceived discrimination. Informal contact with natives was not significantly associated with mental health or perceived discrimination. There was marginally significant evidence (p < .1) that perceived discrimination suppressed the positive association between Dutch language proficiency and mental health. Discussion Greater Dutch language proficiency appears to be beneficial for Somali refugees' mental health, but this effect may partly be cancelled by the associated stronger experiences of discrimination.